Avaliação do impacto de sujidades no desempenho de módulos fotovoltaicos em Minas Gerais - Mariana Myriam Fraga (2018)
Due to concerns with the environment and sustainability, renewable energy sources are an alternative to power supply around the world. The solar photovoltaic energy is a reality in the power supply of special situations (ships, rockets, probes), and it already corresponds to a considerable share in the power matrix of many countries. In Brazil, the installed capacity of photovoltaic energy has been exponentially increased, as a result of Brazilian government program implementations. Because of this expansion, the investigation of external factors that influence the performance of photovoltaic modules is appropriate and motivated, such as the deposited dust on the surface. The present work aims to evaluate the impact of deposited dust in the performance of photovoltaic modules from the Photovoltaic Power Plant Mineirão, located on the soccer stadium Mineirão, in Belo Horizonte, as well as to characterize the material physically and chemically. The plant is composed of 5910 photovoltaic modules of polycrystalline silica. Two groups of modules diametrically opposite were selected and monitored for 43 days, in the second half of the winter of 2016. In each group, a set of modules were separated as reference and maintained clean during the whole study. On day 23, a moderated rainfall occured (7 mm), and on day 30, some additional modules were cleaned. The collected dust were characterized by X-ray diffraction and X-ray fluorescence. The granulometric distribution and the particle shape were also analyzed. The deposited material was responsible for a reduction in peak power of approximately 13.7% in the dry period, and 6.5% in the period after day 23. Dust has also reduced the energy generation in 16.5% in the dry period, and 8% after the rainfall of day 23. The average particle size of the group oriented southwest and northeast were 35.3 ìm and 28.7 ìm respectively. However, this difference was not enough to have an impact on the groups performance. The collected dust was mainly composed of quartz, hematite and calcite. Organic particles were also found. The obtained results reinforce the necessity of periodical cleaning in order to maintain a good performance of power generation.